Odpowiedzi

2010-01-12T22:06:05+01:00
3/a-b + 2/a+b =3(a+b)/[(a-b)(a+b)]+2(a-b)/[(a-b)(a+b)]=
=3a+3b/[(a²-b²)]+2a-2b/[(a²-b²)]=3a+3b+2a-2b/[(a²-b²)]=
5a+b/[(a²-b²)]
Najlepsza Odpowiedź!
2010-01-12T22:06:22+01:00
3/a-b + 2/a+b =3(a+b)/[(a-b)(a+b)]+2(a-b)/[(a-b)(a+b)]=
=3a+3b/[(a²-b²)]+2a-2b/[(a²-b²)]=3a+3b+2a-2b/[(a²-b²)]=
5a+b/[(a²-b²)]
Prosze
1 5 1
2010-01-12T22:09:14+01:00
3/a-b + 2/a+b = 3 (a + b)/ (a - b)* (a+b) + 2 * (a - b) / (a - b)* (a+b) = 3a + 3b/ (a - b)* (a+b) + 2a - 2b /(a - b)* (a+b) = 3a + 3b + 2a - 2b / (a - b)* (a+b) =
5a + b/ (a - b)* (a+b) = 5a + b / a² - b²